Perlindungan Hukum Terhadap Pemenang Lelang Atas Objek Hak Tanggungan yang Telah Dijual Kepada Pihak Ketiga - Wirayanto Natanegara Aswadi; Zainal Muttaqin; Hj. Etty Mulyati (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The execution auction of Mortgage Rights is one of the legal mechanisms for paying off debtors who are in default. In its implementation, the auction minutes as an authentic deed have an important role in providing legal certainty for the auction winner. However, in practice, auction winners often experience obstacles when the auction object has been transferred to a third party, resulting in disputes and uncertainty in the transfer of rights. Based on this, what is the position of the auction minutes in providing certainty and legal protection for auction winners for Mortgage Rights objects that have been sold to third parties? The approach method used in this study uses a normative legal approach. The research specifications used in this study are descriptive analytical. Data analysis was carried out using a qualitative normative approach. The auction minutes have binding legal force and provide legal certainty for auction winners. However, its implementation still faces obstacles in the form of lawsuits from third parties that can disrupt the validity of ownership of auction objects, even though the auction winner has legally obtained the rights. Therefore, auction winners who act in good faith need to get legal protection. In addition, it is necessary to conduct socialization to the public to understand the importance of auction minutes and transparency in the auction process by KPKNL in order to reduce the potential for disputes and clearer regulations are needed regarding legal protection for auction winners to ensure legal certainty in the implementation of auctions.